When the going gets tough, individualizers get going: On the relationship between moral foundations and prosociality. (1st January 2019) - Süssenbach, Philipp; Rees, Jonas; Gollwitzer, Mario
Abstract: Objective: The present research examines the link between moral foundations (Graham et al., 2013; Haidt, 2007) and prosociality. Adopting a person × situation interaction perspective, we suggest that individualizers (whose morality is driven by considerations of harm and justice) act in accordance with their moral values particularly in situations that contain cues of neediness. Method: In Study 1, we measured participants' visual attention toward varying degrees of suffering (within-participants). In Studies 2 and 3 participants were exposed to strong need or not (between-participants) and their moral regard and prosocial intent was assessed. Results: In the face of visual cues of suffering (Study 1) or the presence of strong need (Studies 2 and 3), individualizers reacted with increased attention toward suffering, greater moral responsibility, and stronger prosocial intent. Individuals high on the binding foundations (whose morality is driven by ingroup loyalty, authority, and purity), however, avoided suffering irrespective of its degree (Study 1), did not oblige themselves with moral responsibility (Study 2), and reported reduced prosocial intent in reaction to need (Study 3). Conclusion: An interactionist account of foundation-based prosociality demonstrates that individualizers are likely to help when helping might be perceived as futile, however this potential needs to be activated.